Tillering and Yield Components of Tillers of Some Drought Resistance Paddy Varieties - Bhattacharya, S.N. (Journal of Soil and Water Conservation, 2022)
Tillers which are the antecedents of panicles, are the units of production. Its number and growth directly affect yield. Katyma (1931 and 1951), Matsushima (1956) and Chatterjee (1970) have done some basic work on the tillering pattern of paddy and their contribution to yield. But these works were mainly concerned with normal high-yielding improved varieties. From earlier works (Bhattacharya, 1968), Murthy (1969) and Joshi (1969) it appeared that M. t. u.-17 and Lalnakanda are two very important drought resistant varieties in India.In the present investigation the results of detailed observations made on the initiation of tillers, their growth, development and contributions to yield have been reported.